Characterization of gas phase iron phthalocyanine with X‐ray photoelectron and absorption spectroscopies (Phys. Status Solidi B 6/2015). Issue 6 (June 2015) - Bidermane, Ieva; Lüder, Johann; Totani, Roberta; Grazioli, Cesare; de Simone, Monica; Coreno, Marcello; Kivimäki, Antti; Åhlund, John; Lozzi, Luca; Brena, Barbara; Puglia, Carla
<x xml:space="preserve">Abstract</x> The possibility to design novel functional materials with desired and controlled characteristics demands a thorough understanding of the electronic structure of the building molecules and of the derived molecular materials. Phthalocyanines are versatile molecules, suitable for a variety of technological applications. For example, FePc capability to activate oxygen makes it successfully used in biomimetic catalysis. Since the activation of oxygen seems to take place at the metal center of the molecules, causing a change of the metal ionic state, it is of particular interest to characterize the ionic state of the central metal atom under working/activation conditions. The study carried out by Bidermane et al. (pp. 1259–1265) addresses the issue of identifying the influence of external factors on the electronic structure of the molecules in novel functional materials. The comparison between the electronic properties of gas phase and thick films on surfaces are analyzed by means of XPS and multiplet calculations. These kinds of studies are fundamental for enlightening the purely molecular electronic 'fingerprint' and the modification induced by different working conditions of such molecular films when employed in technological application.